Aluminum exposure affects transferrin-dependent and -independent iron uptake by K562 cells - Pérez, G. (2005)
Aluminum (Al) and iron (Fe) share several physicochemical characteristics and they both bind to transferrin (Tf), entering the cell via Tf receptors (TfR). Previously, we found similar values of affinity constant for the binding of TfR to Tf carrying either Al or Fe. The competitive interaction between both metals prevented normal Fe incorporation into K562 cells and triggered the upregulation of Fe transport. In the present work we demonstrated that Al modified Fe uptake without affecting the expression of Tf receptors. Both TfR and TfR2 mRNA levels, evaluated by RT-PCR, and TfR antigenic sites, analyzed by flow cytometry, were found unchanged after Al exposure. In turn, Al did induce upregulation of non-Tf bound Fe (NTBI) uptake. This modulation was not due to intracellular Fe decrease since NTBI transport proved not to be regulated by Fe depletion. Unlike its behavior in the presence of Tf, Al was unable to compete with NTBI uptake, suggesting that both metals do not share the same alternative transport pathway. We propose that Al interference with TfR-mediated Fe incorporation might trigger the upregulation of NTBI uptake, an adaptation aimed at incorporating the essential metal required for cellular metabolism without allowing the simultaneous access of a potentially toxic metal. © 2004 Elsevier B.V. All rights reserved.